ANALISIS BIAYA TERHADAP PENERIMAAN USAHATANI JAGUNG MANIS DI DESA SEBEMBAN KECAMATAN MUARA WIS - Drianti, Astik; Aida, Nur (Jurnal Magrobis, 2017)
The research aimed was to determine cost factors that affected to the revenue of sweet corn in Sebemban, MuaraWis district. Used cost theories, with observed variables lease for land area, seed, labor, fertilizer, and pesticide.These researched uses primary data obtained from farmers through direct interviews using questionnaires. Sampling technique using proportionate stratified random sampling method with sample number 57 farmers. The magnitude of cost affecting the revenue rate of sweet corn is analyzed by multiple regression analysis.The results showed the cost factors (land area, seed, labor, fertilizer, and pesticide) simultaneously have a positive and significant effect on sweet corn revenue. Land and fertilizer have a positive and significant effect on sweet corn revenue, while seed, labor, and pesticide have no significant effect on sweet corn revenue.Keywords : Sweet corn, Cost factors, Revenue